Construction Project Scheduling Optimization with Critical Path Method (CPM) and Precedence Diagram Method (PDM) (Case Study: PT Samara Insan Sentosa) - Aji, Nuke Maheswara; Nindiani, Aina; Tri Sasmi, Weni; Fadli Perdana, Mohammad (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2025)
Delays in construction projects often occur due to suboptimal scheduling, which results in increased costs and decreased efficiency. PT Samara Insan Sentosa faces a similar problem, where the planned project duration does not match the realization in the field. This study aims to optimize project scheduling using the Critical Path Method (CPM) and Precedence Diagram Method (PDM). The research methods used include secondary data analysis, interviews, and scheduling calculations with both methods. The results of the study show that CPM and PDM can identify critical paths and optimize project completion duration. A comparison of the two methods shows that PDM is more flexible than CPM, with a shorter project completion duration. Implementation of the PDM method can reduce project completion time without sacrificing the quality of work. The conclusion of this study is that scheduling optimization using the right method can increase project efficiency and reduce the risk of delays. The impact of this study can help companies improve the effectiveness of project management.